Seminal Plasma Does Not Influence Canine Semen Stored at 5 degrees C for Long-Term Conservation - Araujo, Michelle Silva [UNESP]; Oliveira Henriques Paulo, Otavio Luis de [UNESP]; Paulini, Fernanda; Souza Ramos Angrimani, Daniel de; Tsunemi, Miriam Harumi [UNESP]; Paula Freitas Dell'Aqua, Camila de [UNESP]; Papa, Frederico Ozanam [UNESP]; Souza, Fabiana Ferreira de [UNESP] (Mary Ann Liebert, Inc, 2021)
Seminal plasma has several components that protect the sperm cells and assist in the fertilization process. In contrast, the exact role carried out by seminal plasma during the cooling of canine semen remains controversial. Moreover, concerning the long estrus period, the possibility to store chilled semen at 5 degrees C for more than 72 hours and maintain good sperm quality for additional inseminations could increase fertilization rates. Thus, this study aimed to evaluate the seminal plasma influence on quality and oxidative stress of the extended canine semen stored at 5 degrees C for 7 days. Three ejaculate pools from eight healthy dogs were collected by digital manipulation of the penis. The sperm kinetics, sperm vitality (eosin/nigrosin stain), integrity of plasma and acrosomal membranes, morphology, superoxide and hydrogen peroxide production, mitochondrial potential, lipid peroxidation, and oxygen reactive species production (induced and spontaneous thiobarbituric acid [thiobarbituric acid reactive substances, TBARS] assay) were evaluated every 48 hours (M0, M48, M96, and M168) until 7 days (168 hours) in cooled extended (TRIS egg yolk) semen of dogs at 5 degrees C with (+SP) or without (-SP) autologous seminal plasma. No statistical difference was found for sperm kinetics in cooled samples with +SP and -SP during the experimental time period, except for the progressive motility of +SP samples that was higher at M48 than M96 (p = 0.023). The seminal plasma did not influence any other evaluated sperm characteristics. Finally, our results demonstrated that the presence or lack of seminal plasma during cooling the semen of dogs does not influence sperm quality at 5 degrees C. Moreover, the components of the semen extender may contribute to maintaining good sperm quality and low reactive oxygen species production during the long period of the dog's semen cooling, even after semen centrifugation.
Keywords: chilled; oxidative stress; dog; spermatozoa